KOMPETENSI DASAR DI SEKTOR TRANSPORTASI LAUT DAN LOGISTIK - Tri Mulyono; Kencana Verawati (Universitas Negeri Jakarta, 2021)
The highest development in the marine transportation and logistics sector at this time is adapting to Industry 4.0. Logistic productivity without involving comptencies human resources with expertise is inevitable. Including the development of technology, information and computers. A cluster of related knowledge, skills, and abilities that affects a role or responsibility, that correlates with performance on the job, that can be measured against well accepted standards, and that can be improved via training and development are comptencies needed in marine transportation and logistics sector. Based on literature from various books, journals and websites that are searched on the internet to answer the question of what competency is needed and why it is needed? The aim of research is to understand or explain basic competencies for logistics experts. The research is explanatory research. The basic competencies for logistics experts are (1) individual competencies as soft skill is represent personal attributes, and (2) academic competencies are critical competencies primarily learned in a school setting include cognitive functions and thinking styles.